PENGARUH KOMPETENSI, INDEPENDENSI, PROFESIONALISME AUDITOR, PENGALAMAN KERJA, PERILAKU DISFUNGSIONAL DAN KOMITMEN ORGANISASI TERHADAP KUALITAS AUDIT PADA KANTOR AKUNTAN PUBLIK DI BALI - Anastasia Ni Made Natalina; Komang Fridagustina Adnantara; Ni Made Ernila Junipisa (Universitas Triatma Mulya, 2022)
Audit quality is the implementation of audits in accordance with standards so that the auditor is able to carry out the duties and responsibilities of an auditor's profession. The rise of financial scandals that occur affects the confidence of users of financial statements and causes a decline in audit quality. The purpose of this study was to obtain empirical evidence that competence, independence, auditor professionalism, work experience, dysfunctional behavior and organizational commitment can affect audit quality. The population of this research is all auditors who work in Public Accounting Firms in Bali. Sampling technique using Porposive Sampling. The sample used in this study were 62 respondents. The data analysis technique used is multiple linear regression analysis. The conclusion obtained is that competence has a positive and significant effect on audit quality, independence has a positive and significant effect on audit quality. Auditor professionalism has a positive and significant effect on audit quality. Work experience has a positive and significant effect on audit quality. Dysfunctional behavior has a negative and significant effect on audit quality. Organizational commitment has a positive and significant effect on audit quality.